Penerapan Pendekatan Understanding by Design Berbasis Assemblr Edu terhadap Hasil Belajar IPAS Siswa Kelas V SD Negeri 7 Parittiga - Paini, Alpaini Himarika; Firdaus, Masagus; Rosmiyati, Evi (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2025)
This study aims to determine whether there is an effect of implementing the Understanding by Design (UbD) approach based on Assemblr EDU on the learning outcomes of Science and Social Studies (IPAS) among grade V students at SD Negeri 7 Parittiga, compared to students who were not taught using this approach. The research method used is quantitative, with a type of Quasi-Experimental Design in the form of a Nonequivalent Control Group Design. The population in this study consisted of all grade V students at SD Negeri 7 Parittiga. The sampling technique used is non-probability sampling, specifically census/total sampling. Based on the data analysis results, the value of t-count > t-table (2.253 > 2.024), thus H₀ is rejected and Hₐ is accepted. Likewise, the significance value (2-tailed) = 0.030 < 0.05. This indicates that there is a significant effect of implementing the Understanding by Design (UbD) approach based on Assemblr EDU on the IPAS learning outcomes of grade V students at SD Negeri 7 Parittiga compared to those not taught using this approach. Therefore, the implementation of the Understanding by Design approach based on Assemblr EDU is effective in improving the IPAS learning outcomes of grade V students.